Wild Cherry tree (Prunus avium L.) growth in pure and mixed plantations in South America - Loewe M., Verónica (2013)
Seven-year-old pure and mixed-species plantations containing cherry tree (Prunus avium L.) were analyzed at six sites in the central and southern area of Chile. The study examines the growth, pests, diseases, and stem form of cherry trees in mixtures and monocultures. Compared to pure plantations, mixed plantations had higher cherry height (up to 28%) in 5 out of 6 sites and higher cherry DBH (up to 34.5%) in 4 out of 6 sites, which could be attributed to a combination of effects, including the presence of nitrogen ﬁxing species. Companion species can play an important role in cherry cultivation. With the exception of piche (Fabiana imbricata Ruiz & Pav.), cherry tree growth was faster and had better sanitary conditions in mixtures than in monocultures. Treatment (species associations) and environment interaction was signiﬁcant, indicating the presence of different mechanisms underlying plantation effects at different sites, and the convenience of carefully identifying the characteristics of main and companion species, as well as site conditions, to propose suitable site-speciﬁc designs for mixed plantations. The growth characteristics of companion and primary species, as well as site conditions, should be selected and matched to improve plantation performance.